Shared micromobility: The influence of regulation on travel mode choice. (13th May 2020) - Lo, Dominic; Mintrom, Chelsea; Robinson, Kate; Thomas, Ryan
Abstract: Shared micromobility, in the form of e‐scooter sharing systems, was introduced to New Zealand (NZ) in late 2018 without a consistent national regulatory framework. This article reflects on the relationship between potential scooter‐share regulations and ridership. Examples of scooter‐share regulations overseas and existing research into similar bicycle‐ and moped‐sharing systems were synthesised into a framework for analysis. Results from an online survey in NZ suggested that regulations governing user behaviour have a negative effect on scooter‐share usage. They also indicated that micromobility technology in the right regulatory environment may offer social, environmental, and transport equity benefits.